Dose calculation and treatment plan optimization including imaging dose from kilovoltage cone beam computed tomography. (1st June 2014) - Alaei, Parham; Spezi, Emiliano; Reynolds, Margaret
Abstract: Background. With the increasing use of cone beam computed tomography (CBCT) for patient position verification and radiotherapy treatment adaptation, there is an increasing need to develop techniques that can take into account concomitant dose using a personalized approach. Material and methods. A total of 20 patients (10 pelvis and 10 head and neck) who had undergone radiation therapy using intensity modulated radiation therapy (IMRT) were selected and the dose from kV CBCT was retrospectively calculated using a treatment planning system previously commissioned for this purpose. The imaging dose was added to the CT images used for treatment planning and the difference in its addition prior to and after the planning was assessed. Results. The additional isocenter dose as a result of daily CBCT is in the order of 3–4 cGy for 35-fraction head and neck and 23–47 cGy for 25-fraction pelvis cases using the standard head and neck and pelvis image acquisition protocols. The pelvic dose is especially dependent on patient size and body mass index (BMI), being higher for patients with lower BMI. Due to the low energy of the kV CBCT beam, the maximum energy deposition is at or near the surface with the highest dose being on the patient's left side for the head and neck (∼ 7 cGy) and on the posterior for the pelvic cases (∼ 80 cGy). Addition of imaging dose prior to plan optimization resulted in an average reduction of 4% in the plan monitor units and 5% in the number of control points. Conclusion. Dose from daily kV CBCT has been added to patient treatment plans using previously commissioned kV CBCT beams in a treatment planning system. Addition of imaging dose can be included in IMRT treatment plan optimization and would facilitate customization of imaging protocol based on patient anatomy and location of isocenter.